Do Labor Intensive Industries Generate Employment? Evidence from firm level survey in India - Deb Kusum Das; Gunajit Kalita (Indian Council for Research on International Economic Relations (ICRIER), 2009)
This study attempts to address the issue of declining labour intensity in India's organized manufacturing in order to understand the constraints on employment generation in the labour intensive sectors. Using primary survey data covering 252 labour intensive manufacturing-exporting firms across five sectors-apparel, leather, gems and jewellery, sports goods, and bicycles for 2005-06 an attempt is made to find out the factors which constrain employment generation in labour intensive firms. The study shows several constraints in the path of employment generation in labour intensive sectors-non-availability of trained skilled workers, infrastructure bottlenecks, low levels of investment, labour rules and regulations, and a noncompetitive export orientation. The study suggests a set of policy initiatives to improve the employment potential of these sectors.
Keywords: E24; J24; J31; D24; 330; Indian Organized Manufacturing; Labor Intensity; Employment Growth; Skilled workforce; Wage structure; Export status; Machinery Usage; Labor laws; South Asia; Arbeitsproduktivität; Arbeitskosten; Industrie; Beschäftigungseffekt; Qualifikation; Lohnstruktur; Arbeitsrecht; Indien; Südasien